دور التسويق المصرفي في زيادة القدرة التنافسية للمصارف دراسة ميدانية على المصارف التجارية في الساحل السوري - قاسم, سامر; نصّور, ريزان; عيسى, يارا حكمت (Latakia University Journal - Economic and Legal Sciences Series, 2015)
يتناول البحث دور التسويق المصرفي في زيادة القدرة التنافسية للمصارف التجارية السورية من خلال دراسة العلاقة بين كل من (الخدمات المصرفية والتسعير والترويج والتوزيع) وزيادة القدرة التنافسية لهذه المصارف. وكذلك دراسة الاختلاف بين المصارف التجارية العامة والخاصة في استخدامها لعناصر المزيج التسويقي المصرفي. اعتمد البحث على المنهج الوصفي, وشمل مجتمع البحث جميع العاملين في المصارف التجارية العامة والخاصة في الساحل السوري, والبالغ عددهم (527) عاملاً, تمّ توزيع (222) استبانة على العاملين تمّ تحديدها باستخدام قانون العينة الإحصائي أعيد منها (204) استبانة بنسبة استجابة بلغت (91.89%), وتوزعت الاستبانات بين (129) استبانة للمصارف العامة, و(75) استبانة للمصارف الخاصة. وباستخدام الأساليب الإحصائية المناسبة تمّ التوصل إلى النتائج الآتية: 1- وجود علاقة طردية ومقبولة ذات دلالة بين استخدام مزيج الخدمات المصرفية في المصارف التجارية وقدرتها على المنافسة في السوق المصرفية. 2- وجود علاقة طردية وضعيفة ذات دلالة بين استخدام كل من (تسعير الخدمات المصرفية, الترويج للخدمات المصرفية, توزيع الخدمات المصرفية) في المصارف التجارية وقدرتها على المنافسة في السوق المصرفية. 3- عدم وجود فروق جوهرية بين المصارف العامة والخاصة في استخدامها لعناصر المزيج التسويقي المصرفي (الخدمات المصرفية, التسعير, الترويج, التوزيع) لتعزيز قدرتها على المنافسة في السوق المصرفي. This paper deals with the role of marketing in the banking system to increase the competitiveness of the Syrian commercial banks through the study of the relationship between each of the (banking services, pricing, promotion and distribution) and increasing the competitiveness of these banks. As well as the study of the difference between the commercial banks in the public and private use of the elements of the marketing mix banking. The research on the descriptive approach, and included the research community all employees in commercial banks, public and private in the Syrian coast, totaling (527) factor, were distributed (222) identification of the workers have been identified using the law of the sample statistical re-ones (204) questionnaire response rate (91.89%), and the questionnaires were distributed between the (129) questionnaire for public banks, and (75) the identification of the private banks. And using appropriate statistical methods was reached the following results: There is a direct correlation and acceptable significant correlation between the use of a combination of banking services in the commercial banks and their ability to compete in the banking market. The existence of a positive relationship and a weak significant differences between the use of each of (the pricing of banking services, the promotion of banking services, distribution services, banking) in commercial banks and their ability to compete in the banking market. The lack of significant differences between public and private banks in the use of the elements of the marketing mix banking (banking services, pricing, promotion, distribution) to enhance their competitiveness in the banking market.